Fractures after stroke—A Danish register‐based study of 106 001 patients. (9th October 2019) - Kristensen, Jonas; Birn, Ida; Mechlenburg, Inger
Abstract : Objectives: To estimate the incidence of fractures, possibly caused by falls, in patients aged 65 and older with first episode of stroke, and to estimate the incidence of fracture types for this group of patients. Another objective was to investigate stroke severity and marital status, as risk factors for fractures. Materials and methods: A large retrospective dataset of 116 519 patients with first episode of stroke was extracted from the Danish Stroke Registry between January 2003 and December 2017. The occurrence of fractures was identified in the Danish National Patient Registry. A univariate analysis was conducted and a multivariate analysis was conducted to determine the relationship between stroke severity and fractures, and marital status and fractures, adjusting for multiple confounders. Cox regression with time‐varying covariates was used, taking time‐dependent variables into account. Results: The incidence rate of fractures post‐stroke was 41.07 per 1000 person‐years between 2003 and 2017 in Denmark. A total of 15 872 (14.86%) sustained a fracture and the mean time at risk until outcome was 3.67 years post‐stroke. Femur fracture was the most common fracture type. Mild, moderate, severe, and unknown stroke severity are associated with fractures after stroke compared to very severe stroke, and living alone at the time of stroke is associated with fractures after stroke compared to living with someone. Conclusions: The incidence rate of fractures in Denmark was 41.07 per 1000 person‐years. Moreover, mild, moderate, and severe stroke severity, and living alone at the time of stroke were found to be risk factors for fracture.